An Analysis of the Moral Transformation and Character Development of the Beast in Beauty and the Beast Movie (2017) Based on Ethical Theory - Arvin Liliana; Imza Resti Kirana Dewi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study analyzes Beast’s character development in a modern adaption of a classic tale, focusing on goodness, love, and, redemption from an ethical prespective. Using descriptive qualitative analysis and film text analysis, the research examines narrative, dialogue, and character interactions, particularly in scenes highlighting Beast’s moral transformation. The analysis is based on Aristotle’s virtue ethics and Kant’s deontological ethics. The findings reveal that Beast’s transformation, driven by love and redemption through his relationship with Belle, demonstrates a shift from selfishness to empathy and moral responsibility. This change results from both external influences and internal reflection. The study highlights film as a powerful medium for conveying moral messages and deepening the understanding of character-driven moral transformation in visual narratives.